2019
DOI: 10.1038/s41467-019-12361-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic adaptations and correlates of survival to immune checkpoint blockade

Abstract: Despite remarkable success of immune checkpoint inhibitors, the majority of cancer patients have yet to receive durable benefits. Here, in order to investigate the metabolic alterations in response to immune checkpoint blockade, we comprehensively profile serum metabolites in advanced melanoma and renal cell carcinoma patients treated with nivolumab, an antibody against programmed cell death protein 1 (PD1). We identify serum kynurenine/tryptophan ratio increases as an adaptive resistance mechanism associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
141
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(149 citation statements)
references
References 21 publications
3
141
0
Order By: Relevance
“…Given the mouting evidence that high IDO expression can lead to inhibition of the effector function of T cells, either directly or indirectly through non-T cell components 36,37 , strategies to effectively target this metabolic pathway can reverse tumor immune resistance mechanisms. Interestingly, increases in the IDO/TDO-product Kyn in the serum of patients receiving anti-PD-1 were recently reported as an adaptive resistance mechanism associated with worse overall survival 13,38 . Similarly, we here found that upregulation of Kyndegrading enzymes correlates with good response to anti-PD-1 therapy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given the mouting evidence that high IDO expression can lead to inhibition of the effector function of T cells, either directly or indirectly through non-T cell components 36,37 , strategies to effectively target this metabolic pathway can reverse tumor immune resistance mechanisms. Interestingly, increases in the IDO/TDO-product Kyn in the serum of patients receiving anti-PD-1 were recently reported as an adaptive resistance mechanism associated with worse overall survival 13,38 . Similarly, we here found that upregulation of Kyndegrading enzymes correlates with good response to anti-PD-1 therapy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Immunomonitoring of blood samples can highlight such dynamic shifts in ongoing immune responses. In NSCLC, RCC and melanoma patients the baseline value of systemic Kyn/Trp as well as its dynamics during treatment course were associated with patient outcome (189,193). In this way the Kyn/Trp ratio could be a marker best capturing IDO activity at a specific moment and perhaps could have relevance in therapeutic monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study profiling Kyn/Trp in more than 900 human cancer cell lines demonstrated that secreted Kyn can be attributed to both IDO and TDO expression by tumor cells (195). However, another study observed a correlation of the Kyn/Trp ratio with PD-L1 and IDO but not with TDO mRNA levels in melanoma samples after 4 cycles of anti-PD-1 immunotherapy (193). Nevertheless, the authors argued that additional sources of Trp to Kyn degradation outside the tumor may exist.…”
Section: Ido In the Peripheral Bloodmentioning
confidence: 99%
“…55,56 At last, profiling of advanced melanoma and renal cell carcinoma (RCC) patients showed that Kyn/Trp alterations correlated with overall survival upon administration of nivolumab (a PD-1 blocker). 57 Thus, IDO inhibition stands out as a promising strategy to (re)instance cancer immunosurveillance. Indeed, IDO inhibitors demonstrated their ability to successfully cooperate with immunotherapy, radiotherapy or chemotherapy even in tumors that are normally resistant to conventional treatments.…”
Section: Introductionmentioning
confidence: 99%